Assessing the Environmental Impact of Electricity Consumption Changes in the Riau Islands During COVID-19 - Yosef Adicita; Nurul Ulfah; Iva Yenis Septiariva; I Wayan Koko Suryawan (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The Riau Islands Province in Indonesia was among the regions impacted by the pandemic, which also influenced electricity usage patterns and subsequently, the environmental impact. To assess these environmental impacts, life cycle assessment (LCA) is an effective tool. This research aimed to evaluate the environmental implications both before and during the COVID-19 pandemic, using SimaPro v.9.1.1.7 software and the Environmental Product Declaration (EPD) database for impact analysis. The inventory data showed that in urban areas like Batam City and Tanjung Pinang City, as well as in Bintan Regency, there was a notable decrease in electricity consumption between 2019 and 2020. Electricity is a crucial energy resource for communities, and this was particularly evident during the COVID-19 pandemic. The Riau Islands Province in Indonesia was among the regions impacted by the pandemic, which also influenced electricity usage patterns and subsequently, the environmental impact. The inventory data showed that in urban areas like Batam City and Tanjung Pinang City, as well as in Bintan Regency, there was a notable decrease in electricity consumption between 2019 and 2020. This reduction led to a significant overall decrease in environmental impact. However, it's important to note that this reduction, brought on by the unpredictable nature of the pandemic, may not be sustainable in the long term.